Atomic‐resolution dissection of the energetics and mechanism of isomerization of hydrated ATP‐Mg2+ through the SOMA string method. Issue 6 (7th July 2015) - Branduardi, Davide; Marinelli, Fabrizio; Faraldo‐Gómez, José D.
Abstract : The atomic mechanisms of isomerization of ATP‐Mg 2+ in solution are characterized using the recently developed String Method with Optimal Molecular Alignment (SOMA) and molecular‐dynamics simulations. Bias‐Exchange Metadynamics simulations are first performed to identify the primary conformers of the ATP‐Mg 2+ complex and their connectivity. SOMA is then used to elucidate the minimum free‐energy path (MFEP) for each transition, in a 48‐dimensional space. Analysis of the per‐atom contributions to the global free‐energy profiles reveals that the mechanism of these transitions is controlled by the Mg 2+ ion and its coordinating oxygen atoms in the triphosphate moiety, as well as by the ion‐hydration shell. Metadynamics simulations in path collective variables based on the MFEP demonstrate these isomerizations proceed across a narrow channel of configurational space, thus validating the premise underlying SOMA. This study provides a roadmap for the examination of conformational changes in biomolecules, based on complementary enhanced‐sampling techniques with different strengths. © 2015 Wiley Periodicals, Inc. Abstract : The mechanisms of isomerization of ATP‐Mg 2+ in solution are examined with three complementary enhanced‐sampling simulation methods. The recently developed String Method with Optimal Molecular Alignment is used to identify and characterize the minimum free‐energy paths for the major conformational transitions of the complex, in a 48‐dimensional space. This analysis reveals the driving forces controlling these isomerization mechanisms at single‐atom resolution.